2017
DOI: 10.1037/hea0000418
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle intervention effects on the frequency and duration of daily moderate–vigorous physical activity and leisure screen time.

Abstract: Objective How a healthy lifestyle intervention changes the frequency and duration of daily moderate-vigorous physical activity and sedentary behavior has not been well-characterized. Secondary analyses of data from the Make Better Choices randomized controlled trial were conducted to evaluate how interventions to increase physical activity or reduce leisure screen time affected the frequency and duration of these behaviors during treatment initiation and follow-up. Methods Participants were 202 adults who ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…42 The behaviour of reducing screen time could have continued not only after the intervention but also until follow-up, which may have led to the reduction in sedentary behaviour. A previous study 43 found similar results to that of this study, suggesting that decreasing screen time can easily be continual. In contrast, moderate-to-vigorous-intensity physical activity was significantly different between the two groups after the intervention but not at follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…42 The behaviour of reducing screen time could have continued not only after the intervention but also until follow-up, which may have led to the reduction in sedentary behaviour. A previous study 43 found similar results to that of this study, suggesting that decreasing screen time can easily be continual. In contrast, moderate-to-vigorous-intensity physical activity was significantly different between the two groups after the intervention but not at follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…Future research could apply methods like EMA, as it might allow for a more in depth test of the covariations and sequentially between health behaviors at different time scales (Dunton, 2018;Conroy et al, 2017). Notably, this would allow for assessment of how different measurement intervals (i.e., days, weeks, months, years)…”
Section: Study Strengths Limitations and Perspectivesmentioning
confidence: 99%
“…Gardner et al [20] acknowledged that self-monitoring, and reforming the social and physical environment are the most encouraging strategies for human behavior change besides recommending environmental reorganization, persuasion, and education to improve self-regulation skills. Intervention design to improve physical activity levels and reduce sedentary time varies significantly in content and effectiveness [20][21][22]. Mobile applications used to improve young people's physical activity should include personalized feedback and provide guidance [14].…”
Section: Motivationmentioning
confidence: 99%